2019
DOI: 10.1021/acs.joc.9b02104
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 3D Antioxidants with Nucleosides as the Core: Inhibition of DNA Oxidation

Abstract: We herein attach ferulic and caffeic acids to −OH and −NH 2 in cytidine, uridine, adenosine, or guanosine for achieving antioxidative hybrids with three-dimensional (3D) configuration. In the case of molecular docking computation, the nucleoside antioxidants with 3D configuration facilitate to bind with the groove of DNA and to cover the surface of a DNA helix. Experimentally, the antioxidative effects of nucleoside hybrids are measured in the inhibition of DNA oxidation caused by 2,2′-azobis(2-amidinopropane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Recently, we have found that four caffeic acids attaching to three -OHs and one -NH 2 of cytidine exhibit antioxidative effect more than 4-fold higher than a single caffeic acid in the protection of DNA against radicalmediated oxidation. [49] Therefore, three-dimensional configuration is beneficial for the antioxidant being recognized by the DNA strand. Along with our findings on the antioxidative effects resulting from the Ugi 4CR and Passerini 3CR products, it is reasonable to expect that antioxidants constructed by MCRs with steric configuration will take advantage of being recognized by biological microenvironments, and thus, become the most promising candidates for pharmacological screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have found that four caffeic acids attaching to three -OHs and one -NH 2 of cytidine exhibit antioxidative effect more than 4-fold higher than a single caffeic acid in the protection of DNA against radicalmediated oxidation. [49] Therefore, three-dimensional configuration is beneficial for the antioxidant being recognized by the DNA strand. Along with our findings on the antioxidative effects resulting from the Ugi 4CR and Passerini 3CR products, it is reasonable to expect that antioxidants constructed by MCRs with steric configuration will take advantage of being recognized by biological microenvironments, and thus, become the most promising candidates for pharmacological screening.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the steric configurations of biological issue should be taken into consideration in the designing of antioxidative structures. Recently, we have found that four caffeic acids attaching to three ‐OHs and one ‐NH 2 of cytidine exhibit antioxidative effect more than 4‐fold higher than a single caffeic acid in the protection of DNA against radical‐mediated oxidation [49] . Therefore, three‐dimensional configuration is beneficial for the antioxidant being recognized by the DNA strand.…”
Section: Discussionmentioning
confidence: 99%